The Quality of Life of Patients With Cervical Cancer at Dr. Wahidin Sudirohusodo Makassar Hospital - Eta Mardiana; Erfina Erfina; Nurmaulid Nurmaulid (Indonesian Contemporary Nursing Journal, 2016)
Introduction: Cervical cancer is an abnormal growth of cells on the cervix. Women diagnosed with cervical cancer will experience changes in terms of physical, psychological, spiritual, social interaction and also in sexual function. Disability to fulfill these functions will also affect the level of quality of life of patients. This study aims to determine the factors associated with quality of life of patients with cervical cancer at the Hospital Dr. Wahidin  Sudirohusodo. Method: The study design using correlational analytic studies using cross-sectional design. Sampling using accidental sampling, the number of respondents as many as 32 people. The instrument of this study using a questionnaire quality of life and family support. Statistical test used was chi-square with significance level α=0.05, Result: Analysis showed bivariate relationship quality of life with cancer stage p=0.646 (p>α), earnings quality of life with patients p=0.296 (p>α), marital status with quality of life p=0.550 (p>α), education with quality of life p=0.002 (p<α), work with quality of life of p=0.023 (p<α) and family support with quality of life p=0.035 (p<α). Conclusion: There is no relationship between stage of cancer, income, marital status with quality of life, but there is a relationship of education, employment, and family support with quality of life of patients with cervical cancer at the Hospital Dr. Wahidin Sudirohusodo. Because that, the family should be able to provide maximum support to the patient in order to improve quality of life of patients.